ITIKAD BAIK DALAM PERJANJIAN PINJAM UANG PADA KOPERASI PESUT DI TENGGARONG - iin Farlina (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT Farlina Iin, 2014 GOODWILL IN LENDING MONEY TO COOPERATIVE AGREEMENT porpoises in Tenggarong. Seventeen University Faculty of Law in August 1945 Samarinda. Supervisor : (1) Abdul Munif, SH., M. Hum (2) Gabriel Gaja Tukan, SH., Hum.          This study examines the good faith in terms of the borrowing agreement and the money resulting from contracts that were not in good faith.          This research includes normative legal research is descriptive. Both parties must be acting in good faith in carrying out an agreement. There are times when good faith has been fully performed and observed, but the implementation of the agreement is still in a stalemate (deadlock). This is where attention is required towards adherence to an event can be resolved satisfactorily. Of course, as is the case with all items that contain something awards (waardering), compliance is not likely to result in a satisfactory resolution of events every human person, it is not always absolute (relatief), which should be in the thoughts and feelings of the people in charge of completing a events, such as the Judge or Government Agency after watching all the factors, which can be used in a natural state of mind and feelings of the people.          Occur close relationship between the teachings of good faith in the execution of the agreement and the theory of belief at the time the agreement. Good faith (Article 1338 paragraph 3) and propriety (Article 1339) is generally mentioned in the same breath, if the judge after testing the appropriateness of an agreement can not be implemented then it means that the agreement is contrary to public order and morality. Agreement is not only determined by the parties in the formulation of the agreement but also determined by good faith and propriety, so in good faith and propriety were also specify the contents of the agreement. Thus a particular agreement and loan agreement to borrow money if it is not done in good faith (in bad faith), the agreement is contrary to public order and morality and norms applicable law.            In the Book of the Law of Civil Law, the provisions on good faith, particularly with regard to the implementation of the agreement contained in paragraph 3 of Article 1338 which stipulates that all agreements must be implemented in good faith.